2018
DOI: 10.22610/jebs.v9i6.2014
|View full text |Cite
|
Sign up to set email alerts
|

Inflation Dynamics in Algeria

Abstract: In thispaper, we analyze Inflation Dynamics in Algeria between 2002 and 2016. We use a Vector Auto Regressive model (VAR), impulse response functions (IRF) and variance error decomposition (VDC) to uncover possible links between public spending component sand inflation. Wetest for the sources and dynamics of inflation in Algeria by focusing on public spending, since they are expected to exert a strong influence on the aggregate demand and hence inflation. According to the results we found, inflation in Algeria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…Concerning the explanatory variables, the analysis reveals that ER has a significant positive association with CPI in Algeria, Egypt and Tunisia. This result is consistent with ross Mokhtar and Sowaidi (2004), Helmy et al (2018), Mehibel and Yacine (2018), Solieman and El-Naggar (2018), Mouhcene and Manaa (2019), Ali (2021), Dekkiche (2022) and Laourari and Abderrahim (2022). They found that the nominal effective exchange rate determines inflation variations, thus, the effect of a depreciation/devaluation of the domestic currency has a greater impact on inflation than on import prices.…”
Section: Resultssupporting
confidence: 85%
“…Concerning the explanatory variables, the analysis reveals that ER has a significant positive association with CPI in Algeria, Egypt and Tunisia. This result is consistent with ross Mokhtar and Sowaidi (2004), Helmy et al (2018), Mehibel and Yacine (2018), Solieman and El-Naggar (2018), Mouhcene and Manaa (2019), Ali (2021), Dekkiche (2022) and Laourari and Abderrahim (2022). They found that the nominal effective exchange rate determines inflation variations, thus, the effect of a depreciation/devaluation of the domestic currency has a greater impact on inflation than on import prices.…”
Section: Resultssupporting
confidence: 85%